Atherosclerosis in mummified human remains from Vilnius, Lithuania (18th–19th centuries AD): A computed tomographic investigation. Issue 5 (20th June 2014) - Piombino‐Mascali, Dario; Jankauskas, Rimantas; Tamošiūnas, Algirdas; Valančius, Ramūnas; Thompson, Randall C.; Panzer, Stephanie
Abstract : Objective: Through the study of preserved human remains, it is now known that atherosclerosis, commonly thought to be a modern disease, also existed in historic and prehistoric periods. To date, however, little evidence of atherosclerosis has been reported in samples of tissues from spontaneously mummified bodies that are often found in European crypts and churches. Methods: Within the framework of the Lithuanian Mummy Project, whole‐body computed tomographic scans of seven spontaneous mummies from a crypt in Vilnius were obtained and assessed for indications of atherosclerosis. Results: Three of the mummies investigated showed clear evidence of atherosclerosis, which was at times quite severe. Atherosclerosis is believed to have been prevalent among affluent members of Lithuanian society, which is corroborated by historical sources. Conclusions: In accordance with recent, significant data, this study further demonstrates the antiquity of this disease. Documentary and ethnographic data suggest that lifestyle may have played a role in the onset of atherosclerosis in these individuals. Am. J. Hum. Biol. 26:676–681, 2014. © 2014 Wiley Periodicals, Inc.